Penerapan Version control system Berbasis Web Menggunakan Next.JS, Nest.JS, Node.JS, dan MongoDB Pada Proses Pengerjaan Skripsi Mahasiswa - Soplanit, Axsel Riando; Supiyanto, S; Saputro, Agung Dwi; Kmurawak, Remuz MB; Sampebua, Mingsep Rante (STIKOM Tunas Bangsa Pematangsiantar, 2023)
In the education systems, particularly in college, thesis courses are one of the determinants of a student's graduation. However, while working on the thesis, many students are still unable to manage their own thesis files, many factors trigger this to happen, one of which is the number of revisions which causes a loss of enthusiasm in students. This can cause students forget where he/she store the files or accidentally delete their thesis files because they have not been done for a long time. To record the entire history of thesis files, a web-based version control system must be implemented which functions to record the entire history of student thesis files. The web was created using Typescript and Javascript programming languages with the Next.JS and Nest.JS frameworks that run on the Node.JS runtime, for the database using MongoDB. Based on the test results, it is concluded that this system runs well and this system is made very private so that one user cannot enter another user's repository. The system has been tested using black box testing.